Pro Silverlight 3 in C# - MacDonald, Matthew (New York : Apress L. P., 2009)
Annotation Silverlight 3 is the latest iteration of Microsofts cross-browser technology for creating rich user experiences on the web. Like its predecessor, Silverlight 2, it rides atop the .NET Framework for maximum ease of use and coding efficiency. The new technology carries forward much of the work that has been done before and augments it in many important respects, including support for H.264 video, major improvements to the graphics engine (including true 3D rendering) and much richer data-binding options for interfacing with other applications.This second edition of Pro Silverlight in C# carries forward the all the key features that have made the first edition an immediate success. Most notably the book presents all artwork, screenshots and code in full-colour; provides readers with a comprehensive theoretical grounding, and illustrates all concepts with an abundance of fully-worked practical examples.